Paracremonium lepidopterorum, a new insect-associated fungus - Ming, Da-Qiong; Luo, Ling-Yan; He, Xiao-Xia; Wang, Ming-Shu; Fang, Wen-Xing; Chen, Shu-Feng; Chen, Wan-Hao; Han, Yan-Feng; Liang, Zong-Qi (Phytotaxa, 2021)
During a survey of entomopathogenetic fungi from Southwest China, a new species, Paracremonium lepidopterorum was isolated from a pupa. It differs from other Paracremonium species by its shorter cylindrical phialides and absence of slimy head of conidia and chlamydospores. Phylogenetic analyses based on the combined datasets of ITS+LSU+TUB confirmed that P. lepidopterorum is distinct from other species. The new species is formally described and illustrated, and compared to similar species.